If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(y + -5) = -4 Reorder the terms: y(-5 + y) = -4 (-5 * y + y * y) = -4 (-5y + y2) = -4 Solving -5y + y2 = -4 Solving for variable 'y'. Reorder the terms: 4 + -5y + y2 = -4 + 4 Combine like terms: -4 + 4 = 0 4 + -5y + y2 = 0 Factor a trinomial. (1 + -1y)(4 + -1y) = 0Subproblem 1
Set the factor '(1 + -1y)' equal to zero and attempt to solve: Simplifying 1 + -1y = 0 Solving 1 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = 0 + -1 -1y = 0 + -1 Combine like terms: 0 + -1 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1Subproblem 2
Set the factor '(4 + -1y)' equal to zero and attempt to solve: Simplifying 4 + -1y = 0 Solving 4 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1y = 0 + -4 -1y = 0 + -4 Combine like terms: 0 + -4 = -4 -1y = -4 Divide each side by '-1'. y = 4 Simplifying y = 4Solution
y = {1, 4}
| (2x-3)=4x+bx+9 | | (x^2+3)/(x+3)=0 | | y=-1/60x^2+x+66/10 | | ln(2x-5)=1.68 | | C^2-7x=8 | | 15=.5x(2+3) | | (A-2)(a-3)=6 | | X^2+3c-10=0 | | t^2-9t+5=0 | | 0=9(k-0.67)+33 | | 4(w-1)+2(w-2)=4 | | x^2+32*x+4.8=0 | | 0=-16t^2+15t+2 | | 64=42 | | -6b-14+4b=-2 | | -5-15d+1=14d-32 | | 66.5+x=88-29.6 | | -3(2z-7)=18-3z+21-3z | | 0=2x+1-4x+3 | | -7(2x-4)=28 | | (6x^6/2x^4)^-4 | | 27y^2+69y-8=0 | | (X+1)(x-8)+28=3x-1 | | (4x-3)(-5)=75 | | 34p+22p-11p=p+88 | | 5y-7=80-18 | | x^2-mx-12=0 | | X/8+2=5 | | 7x+4x=7 | | -4(2x-1)=-20 | | (x+11)/2=-14 | | -3+x=-4 |